2015
DOI: 10.1007/s00223-015-0059-5
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial to Examine the Effect of 2-Year Vitamin B12 and Folic Acid Supplementation on Physical Performance, Strength, and Falling: Additional Findings from the B-PROOF Study

Abstract: Elevated homocysteine concentrations are associated with a decline in physical function in elderly persons. Homocysteine-lowering therapy may slow down this decline. This study aimed to examine the effect of a 2-year intervention of vitamin B12 and folic acid supplementation on physical performance, handgrip strength, and risk of falling in elderly subjects in a double-blind, randomized placebo-controlled trial. Participants aged ≥65 years with elevated plasma homocysteine concentrations [12–50 µmol/L (n = 291… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 36 publications
2
45
0
Order By: Relevance
“…One study evaluating the effect of a combination of vitamin B12 and folate on endpoints of physical function failed to detect significant improvements in parameters linked to frailty. 58 Our results have demonstrated that the patho-physiological decline of intestinal and renal function of vitamin B12 transport during aging directly contributes to poor vitamin B12 status. It is therefore likely that a proportion of individuals in the elderly population are poorly responsive to vitamin B12 supplementation.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…One study evaluating the effect of a combination of vitamin B12 and folate on endpoints of physical function failed to detect significant improvements in parameters linked to frailty. 58 Our results have demonstrated that the patho-physiological decline of intestinal and renal function of vitamin B12 transport during aging directly contributes to poor vitamin B12 status. It is therefore likely that a proportion of individuals in the elderly population are poorly responsive to vitamin B12 supplementation.…”
Section: Discussionmentioning
confidence: 60%
“…There is only limited evidence for the efficacy of vitamin B12 on frailty parameters, and studies evaluating vitamin B12 in the elderly are often performed in combination with other micronutrients. One study evaluating the effect of a combination of vitamin B12 and folate on endpoints of physical function failed to detect significant improvements in parameters linked to frailty . Our results have demonstrated that the patho‐physiological decline of intestinal and renal function of vitamin B12 transport during aging directly contributes to poor vitamin B12 status.…”
Section: Discussionmentioning
confidence: 60%
“…This study mainly focuses on the elucidation of the metabolic pathways during biomineralization to get an idea of these processes in vivo and in vitro. Previous experiments with seven different B vitamins in different concentrations revealed a positive effect on cell proliferation with increasing concentrations caused by three B vitamins pyridoxal (B 6 ), folic acid (B 9 ), and cobalamine (B 12 ) (Dhonukshe-Rutten et al 2003;Swart et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…vitamin B12 and folate supplementation, have not consistently shown reductions in cognitive decline (40, 41). physical function decline (42), nor reduced risk of cardiovascular disease (43, 44). Alternatively, homocysteine might be a marker of disease severity rather than a causal agent of disease.…”
Section: Discussionmentioning
confidence: 99%